2016
DOI: 10.1614/ws-d-15-00133.1
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Rotations and Optimal Cultural Practices Control Wild Oat (Avena fatua)

Abstract: In western Canada, more money is spent on wild oat herbicides than on any other weed species, and wild oat resistance to herbicides is the most widespread resistance issue. A direct-seeded field experiment was conducted from 2010 to 2014 at eight Canadian sites to determine crop life cycle, crop species, crop seeding rate, crop usage, and herbicide rate combination effects on wild oat management and canola yield. Combining 2× seeding rates of early-cut barley silage with 2× seeding rates of winter cereals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 42 publications
3
40
3
Order By: Relevance
“…An opposite trend was observed for Avena fatua which reduced in importance and particularly declined in permanent crops (-12 points) and alfalfa (-10 points). It probably happened due to the effectively combined diverse and optimal cultural practices and herbicide use against this annual weed (Harker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…An opposite trend was observed for Avena fatua which reduced in importance and particularly declined in permanent crops (-12 points) and alfalfa (-10 points). It probably happened due to the effectively combined diverse and optimal cultural practices and herbicide use against this annual weed (Harker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Establishing alfalfa for only 2 yr of production was not as profitable as other crops. However, canola returns in 2014 after alfalfa were generally high and the wild oat population was low (Harker et al 2016). Yearly alfalfa returns can be high once the crop is established, but there was a cost and forgone income to establish the alfalfa stand and a cost to terminate the alfalfa.…”
Section: Discussionmentioning
confidence: 99%
“…A field study at eight locations in Canada was run from 2010 through 2014 (Harker et al 2016). Six of the sites were in the prairies of western Canada (Edmonton, Lacombe, and Lethbridge, AB; Scott and Saskatoon, SK; Carman, MB) and two were in eastern Canada (New Liskeard, ON; Normandin, QC).…”
Section: Field Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A large-scale research consortium, involving five Canadian provinces from 2010 to 2014, found that combining longer crop rotations that included diverse crop phenologies with optimal crop seeding rates and reduced soil disturbance could create large reductions in herbicide-resistant A. fatua infestations and improve net economic returns to management. 41 Implementation of such an approach at landscape scales would create a shifting mosaic wileyonlinelibrary.com/journal/ps of contrasting crop phenologies across growing seasons, preventing any one weed life history group (e.g., summer annuals) from becoming too entrenched at broad spatial scales. Similar weed management benefits have been found from the diversification of corn-soybean production systems.…”
Section: Law 1: Connectionsmentioning
confidence: 99%